#### Answer

$-8\sqrt 5$

#### Work Step by Step

$(\sqrt 5-5)(2\sqrt 5+2)$
=$\sqrt 5(2\sqrt 5+2)-5(2\sqrt 5+2)$
=$2\sqrt 5\sqrt 5+2\sqrt 5-10\sqrt 5-10$
=$2(5)+2\sqrt 5-10\sqrt 5-10$
=$10+2\sqrt 5-10\sqrt 5-10$
=$10-10+(2-10)\sqrt 5$
=$-8\sqrt 5$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-8\sqrt 5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.